Cloud Security Vulnerabilities and Solution Model - Kouchay, Shouket Ahmad (Review of Computer Engineering Research, 2020)
Cloud computing is the revolution and solution to the computing world which has paid further attention as an emerging network storage technology. Cloud computing has enormous adaptability in terms of demand or availability of resources. The organization prefers cloud storage services to reduce the overhead of storing data locally. Yet, Data security and privacy are the major issues in cloud computing. Although security is still one of the critical challenges in the world of cloud computing. The security concerns comprise the loss of vital information and privacy loss of any individual who uses cloud networking. This research reviews the cloud Security, its vulnerabilities and proposes a three-layer model of AES encryption for Cloud Computing Security and RSA is used to hide the key of the AES. According to our research, this model is one of the most compact encryption which consumes less storage space with short calculation time. A detailed review of cloud security concerns and resolutions has been discussed in this paper.